A quasi-Linear Parameter Varying (qLPV) modeling approach for real time piloted simulation of tiltrotor - Nabi, H.N.; Quaranta, G. (My University, 2019)
Tiltrotors can transform from helicopter configuration to a fixed wing airplane configuration. This allows them to have a broader flight envelope. The dynamics of tiltrotors change with flight condition and aircraft configuration. Therefore, a model stitching technique based on quasi-Linear Parameter Varying (qLPV) framework is employed to develop a continuous full flight envelope flight dynamics model for the purpose of control system design and real time piloted simulation. A high order qLPV model is developed for XV-15 where discrete linear state-space models are stitched together to provide a varying model dynamics and trim characteristics over the complete flight envelope. The model is also coupled with engine dynamics, rotor speed governor, actuator dynamics and stability and control augmentation system (SCAS). Lastly, the qLPV model is implemented in FRAME-Sim, a fixed base rotorcraft flight simulation system.